ANALISA SISTEM KOMUNIKASI DATA PADA SIMULASI ROBOT SEPAK BOLA BERODA - Dwiyanto, Damar; Fath, Nifty (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Internet network can connect every computer that is connected in it, not only sharing information but also enables each computer to do work together, thus allowing users to control other computers. In football robot requires good coordination between robots using decision making or control carried out by one robot that requires data on the environmental conditions of all robots. Therefore we need a reliable data communication system. This research aims to design and analyze a data communication system on a soccer robot team. The method used in this research is to build a communication system between clients and servers using the secure shell (ssh) protocol. The secure shell (ssh) protocol is a network protocol located at the application layer of the TCP / IP protocol, which is used to control computers (remotely), send files, and others. This secure shell (ssh) protocol is used to connect clients and servers to robot simulations using the Robot Operating System (ROS) software as a tool to make robot software and Gazebo software as simulators. The quality of the data communication that was designed was then tested using Wireshark software. The parameters of Quality of Service will be measured between throughput, delay, packet loss, and jitter that refers to the TIPHON standard. Based on the results of testing the data communication system that has been done by placing the machine close to the access point, the average throughput is 28,02619 kbps (very good), an average packet loss of 0% (very good), a delay of 0.28651552697192 ms (very good ), and jitter for 0.00000814 ms (good). Meanwhile testing by placing the machine within 10 meters with an access point obtained an average throughput of 15,44595 kbps (very good), an average packet loss of 0% (very good), a delay of 0.520748991128 ms (very good), and jitter of 0.0000144 ms (good). From the tests conducted showed that the communication system that was made was by the initial plan and the communication system was reliable.